The effects of physical activity on functional MRI activation associated with cognitive control in children: a randomized controlled intervention - Chaddock-Heyman, Laura; Erickson, Kirk I.; Voss, Michelle; Knecht, Anya; Pontifex, Matthew B.; Castelli, Darla; Hillman, Charles; Kramer, Arthur (Frontiers in Human Neuroscience, 2013)
This study used functional magnetic resonance imaging (fMRI) to examine the influence of a 9-month physical activity program on task-evoked brain activation during childhood. The results demonstrated that 8- to 9-year-old children who participated in 60+ minutes of physical activity, 5 days per week, for 9 months, showed decreases in fMRI brain activation in the right anterior prefrontal cortex coupled with within-group improvements in performance on a task of attentional and interference control. Children assigned to a wait list control group did not show changes in brain function. Furthermore, at post-test, children in the physical activity group showed similar anterior frontal brain patterns and incongruent accuracy rates to a group of college-aged young adults. Children in the wait list control group still differed from the young adults in terms of anterior prefrontal activation and performance at post-test. There were no significant changes in fMRI activation in the anterior cingulate cortex for either group. These results suggest that physical activity during childhood may enhance specific elements of prefrontal cortex function involved in cognitive control.